الجذور التاريخية للرمزية في الشعر العربي: بين الأسباب والأهداف - الدبسي، أشرف حسن محمد حسن علي; المقريف، انتصار عمران (جامعة المدينة العالمية, 2016)
The historical roots symbols in the Arab poetry: Reasons and objectives This research is titled: The historical roots of the symbols in the Arab poetry; reasons and objectives. The problem of the research lies in the purposes of the metaphorical expressions in the Arabic poetry; whether metaphors are a Western art that has never been introduced to the Arabic literature; since the purpose is different of that in the Western poetry. This research aims to provide a thorough analysis of its topic through an analytical, inferential and descriptive methodology to study the reasons and objectives of using metaphors in Arabic literature. The study revealed that the main reason for using metaphors in Arabic poetry is the wars and their effects, appearnce of modern poetic school, habits and social values, and translation. The researcher suggested that the most important objectives of the metaphors are concluded in its ability to guide the writers and poets to the creativity in literature; transports them to delve deeper into the language, and search the depths of their ideas for a homeland in their disapora; causing them to make an expression of the language to reveal about feelings and emotions.
هذا البحث جاء بعنوان: الجذور التاريخية للرمز في الشعر العربي الأسباب والأهداف، وإشكالية البحث تكمن في أسباب الرمزية في الشعر العربي وهل الرمز فن غربي لم يعرفه الأدب العربي؛ نظرا لاختلاف أسبابها عن الشعر الغربي، وسيهدف البحث إلى بيان أهم الأسباب الداعية إلى الرمز في الشعر العربي وأهدافه، وسيعالج هذا البحث مادته بواسطة المنهج الوصفي الاستنباطي التحليلي، لأسباب الرمز وأهدافه في الشعر العربي، وتوصل البحث إلى أن أهم أسباب الرمز في الشعر، الحروب وآثارها، والمدارس الشعرية الحديثة، والعادات والقيم الاجتماعية، والترجمة، وتوصل الباحث إلى أن أهم أهداف الرمز، تتلخص في قدرته على توجيه الأدباء والشعراء إل الإبداع الأدبي؛ حيث ينقلهم إلى التعمق في اللغة والبحث في أعماق أفكارهم عن وطن لغربتهم؛ مما يجعلهم يتخذون من لغة الإيحاء تعبيرا لهم عن المشاعر والأحاسيس.
Keywords: الشعر العربي -- الدواوين والقصائد -- نقد الشعر -- الرمزية في الشعر